Use of ultrasound‐guided autologous bone marrow transfer for treatment of suspensory ligament desmitis in 30 race horses (2003–2010). Issue 3 (29th January 2013) - Hall, MS; Vasey, JR; Russell, JW; Russell, T
<x xml:space="preserve">Abstract</x> Objective To evaluate the racing performance of horses that underwent ultrasound‐guided intralesional injection of autologous bone marrow aspirate for treatment of selected forelimb suspensory ligament (body or branch) core lesions. Design Retrospective cohort study of 13 Standardbred and 17 Thoroughbred race horses. Methods Autologous bone marrow aspirated from the sternebrae was injected, under ultrasound guidance, into suspensory ligament core lesions (body or branch). Racing records were reviewed for a comparison of performance before and after surgery. Results Of the 13 Standardbreds, 9 (69%) had one or more starts within the follow‐up period and 9 (69%) had five or more starts. Of the 17 Thoroughbreds, 15 (88%) had one or more starts within the follow‐up period and 12 (71%) had five or more starts. Eight Standardbred horses had at least one start both before and after surgery. Earnings per start did not differ significantly between the three starts immediately after surgery compared with the three starts immediately prior to surgery. Thirteen Thoroughbred horses had at least one start both before and after surgery. Earnings per start were less for the three starts immediately after surgery compared with the three starts immediately prior to surgery. Conclusions and clinical relevance A horse with a core lesion in the branch or body of the suspensory ligament has a good prognosis for return to racing after treatment with intralesional injection of bone marrow aspirate.